Income volatility and health - Timothy J. Halliday (Institute for the Study of Labor (IZA), 2007)
We investigate the impact of exogenous income fluctuations on health using twenty years of data from the Panel Study of Income Dynamics using techniques from the literature on the estimation of dynamic panel data models. Contrary to much of the previous literature on health and socio-economic status, we find that, on average, adverse income shocks lead to a deterioration of health. These effects are most pronounced for working-aged men and are dominated by transitions into the very bottom of the earnings distribution.
Keywords: I0; 360; Gradient; health; dynamic panel data models; recessions; Einkommen; Schock; Arbeitslosigkeit; Sozialer Status; Gesundheit; Morbidität; Schätzung; USA